Efficacy and safety of neoadjuvant immunotherapy plus chemotherapy followed by adjuvant immunotherapy in resectable non-small cell lung cancer: a meta-analysis of phase 3 clinical trials - Zhang, Wenjing; Liang, Zhanpeng; Zhao, Yurong; Li, Yanwei; Chen, Ting; Li, Wenxia; Chen, Yunqi; Wu, Peiye; Zhang, Huatang; Fang, Cantu; Li, Luzhen (Frontiers in Immunology, 2024)
Objective At present, several important trials have been published show that perioperative immunotherapy combined with chemotherapy can improve the prognosis of patients with resectable non-small cell lung cancer, which further optimizes treatment options. Therefore, we conducted a systematic review and meta-analysis to evaluate the efficacy and safety of perioperative immunotherapy combined with chemotherapy in resectable non-small cell lung cancer. Methods The following databases were searched for relevant studies: PubMed, EMBASE, Cochrane library (updated 12 October 2023). All randomized trials comparing perioperative immunotherapy combined with chemotherapy versus chemotherapy alone in resectable non-small cell lung cancer were eligible for inclusion. Data were analyzed using Review Manager 5.4.1 (Cochrane collaboration software). Primary outcomes and measures included overall survival (OS), event-free survival (EFS), pathological complete response (pCR), major pathological response (MPR), R0 resection rate, rate of underwent surgery and adverse events (AEs). Results A total of 2912 patients (1453 receiving perioperative immunotherapy plus chemotherapy and 1459 receiving chemotherapy alone) were included in this systematic review and meta-analysis. The result showed that compared with chemotherapy alone, combined therapy significantly improved OS (HR = 0.68;95% CI: 0.56-0.83), EFS (HR = 0.58;95% CI: 0.51-0.65), pCR (OR = 7.53;95% CI: 4.63-12.26), MPR (OR = 5.03;95% CI: 3.40-7.44), R0 resection (OR = 1.58;95% CI: 1.152.18) and rate of underwent surgery (OR = 1.25;95% CI: 1.04-1.49). However, combination therapy was associated with higher risk of severe adverse event (OR = 1.46;95% CI: 1.19-1.78; P=0.0002), grade 3 and higher treatment-related adverse event (TRAE) (OR = 1.25;95% CI: 1.06-1.49; P=0.010), TRAE that led to interruption (OR = 1.90;95% CI: 1.34-2.68; P=0.0003) and immune-related adverse event (OR = 2.78;95% CI: 2.18-3.55; P<0.00001). Significant benefits were observed across most subgroups of EFS and pCR. However, no statistical differences were observed for EFS of never smoked (HR = 0.73;95% CI: 0.51-1.05) and EGFR-mutation positive (HR = 0.35;95% CI: 0.04-3.03). Conclusion This systematic review and meta-analysis found superior efficacy associated with perioperative immunotherapy plus chemotherapy compared with chemotherapy alone in both tumor regression and prolonged survival in resectable NSCLC, but increased the risk of TRAE, so monitoring for adverse events is warranted. Systematic review registration https://www.crd.york.ac.uk/prospero, identifier (CRD42023476786).